(untitled) (Atlas Journal of Biology, 2017)
In the course of work on the taxonomy and agronomy of Mirabilis expansa (Ruiz and Pav.) Standl. (Nyctaginaceae), it became clear that there is no thorough published review of the medicinal and other useful aspects of the family. This work illustrates the history and potential for use for Nyctaginaceae at the generic level world-wide. Several genera in this family have well documented potential as sources of medication, food, dye, lumber and adhesives. Abronia, Boerhavia, and Mirabilis are reported most often for positive laboratory assay results. Pisonia and Neea have both been used as sources of lumber in the tropics. In addition, Bougainvillea and Mirabilis have been utilized for floriculture. Included, is an updated analysis of the historical confusion between medicinal Mirabilis jalapa L. and medicinal Jalap in the Convolvulaceae, and the disagreements over taxonomic names in both families which have contributed to this error and detracted from its resolution. Known invasive issues for some Nyctaginaceae species are discussed, having economic impact on agriculture. A recommendation is made that highly variant expression in Nyctaginaceae taxa makes them strong candidates for investigation of polyploidy and epigenetic patterns, important for better understanding evolution and development in plants.